2010
DOI: 10.1038/jcbfm.2010.173
|View full text |Cite
|
Sign up to set email alerts
|

Striatal and Cortical BOLD, Blood Flow, Blood Volume, Oxygen Consumption, and Glucose Consumption Changes in Noxious Forepaw Electrical Stimulation

Abstract: Recent reports showed noxious forepaw stimulation in rats evoked an unexpected sustained decrease in cerebral blood volume (CBV) in the bilateral striatum, whereas increases in spike activity and Fos-immunoreactive cells were observed. This study aimed to further evaluate the hemodynamic and metabolic needs in this model and the sources of negative functional magnetic resonance imaging (fMRI) signals by measuring blood oxygenation-level-dependent (BOLD), cerebral-blood-flow (CBF), CBV, and oxygen-consumption (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 42 publications
(66 reference statements)
6
50
0
1
Order By: Relevance
“…In a series of studies, Shih and collaborators characterized a counter-intuitive negative BOLD signal change in the striatum of the rat in the face of increased neuronal activity caused by pain and exacerbated by morphine treatment during a noxious stimulus (Shih et al, 2009, 2011, 2012). The effect of morphine was blocked with naloxone pretreatment, evidence of opioid receptor involvement.…”
Section: Discussionmentioning
confidence: 99%
“…In a series of studies, Shih and collaborators characterized a counter-intuitive negative BOLD signal change in the striatum of the rat in the face of increased neuronal activity caused by pain and exacerbated by morphine treatment during a noxious stimulus (Shih et al, 2009, 2011, 2012). The effect of morphine was blocked with naloxone pretreatment, evidence of opioid receptor involvement.…”
Section: Discussionmentioning
confidence: 99%
“…1 It plays a pivotal role in several neurodegenerative disorders and regulating motor behavior. Recent reports showed that unilateral noxious forepaw electrical stimulation in rats evoked sustained negative blood oxygenation level dependent (BOLD), cerebral blood flow (CBF), and cerebral blood volume (CBV) functional magnetic resonance imaging (fMRI) responses in the bilateral striatum with no significant difference between two hemispheres, [2][3][4][5][6] while the neuronal spike and c-Fos activities increased. 6 This negative response has also been observed in epileptic rats during whisker stimulation 7 or normal rats during direct nerve stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…Contralateral CPu (cCPu) response was not recorded because of our hardware limitation and the fact that no difference was detected between the two hemispheres in this model. [2][3][4][5][6] To investigate whether the striatal negative fMRI response can serve as a marker for striatal functional integrity, we used stimulation of 10 mA, 3 milliseconds pulse width, and 12 Hz in two groups of rats underwent 20-and 45-minute middle cerebral artery occlusion (MCAO) and followed the fMRI responses up to 28 days.…”
Section: Introductionmentioning
confidence: 99%
“…This is a relatively small group size, but not uncommon for small-animal PET imaging studies (Barbarich-Marsteller et al, 2005;Higuera-Matas et al, 2008;Soto-Montenegro et al, 2009;Shih et al, 2011).…”
Section: Subset Selectionmentioning
confidence: 99%